Incidence and 30-day case fatality for acute myocardial infarction in England in 2010: national-linked database study. - Smolina, K; Wright, F; Rayner, M; Goldacre, M (2012)
BACKGROUND: There are limited national population-based epidemiological data on acute myocardial infarction (AMI) in England, making the current burden of disease, and clinical prognosis, difficult to quantify. The aim of this study was to provide national estimates of incidence and 30-day case fatality rate (CFR) for first and recurrent AMI in England. METHODS: Population-based study using person-linked routine hospital and mortality data on 79 896 individuals of any age, who were admitted to hospital for AMI or who died suddenly from AMI in 2010. RESULTS: Of 82 252 AMI events in 2010, 83% were first. Age-standardized incidence of first AMI per 100 000 population was 130 (95% CI 129-131) in men and 55.9 (95% CI 55.3-56.6) in women. Age-standardized 30-day overall CFRs including sudden AMI deaths for men and women, respectively, were 32.4% (95% CI 32.0-32.9) and 30.3% (95% CI 29.8-30.9) for first AMI and 29.7% (95% CI 28.7-30.7) and 26.7% (95% CI 25.5-27.9) for recurrent AMI. Age-standardized hospitalized 30-day CFR was 12.0% (95% CI 11.6-12.3) for men and 12.3% (95% CI 11.9-12.7) for women. CONCLUSIONS: While the majority of AMIs are not fatal, of those that are, two-thirds occur as sudden AMI deaths. About one in six of all AMIs are recurrent events. These findings reinforce the importance of primary and secondary prevention in reducing AMI morbidity and mortality.